The transformation of the content of academic disciplines as a prerequisite for the preparation of a competent professional (Pedagogy of Higher and Secondary Education, 2012)
Panisheva O. The transformation of the content of academic disciplines as a prerequisite for the preparation of a competent professional.In article ways of transformation of the contents of discipline «Вases of algorithmization and the mathematical logic» for the purpose of formation professional competences the future engineers- programmers and teachers of computer science are considered.
Keywords: competence; contents of training; professional orientation; training of teachers; the mathematical logi